2013
DOI: 10.1111/mec.12410
|View full text |Cite
|
Sign up to set email alerts
|

Host specificity shapes population structure of pinworm parasites in Caribbean reptiles

Abstract: Host specificity is one of the potential factors affecting parasite diversification because gene flow may be facilitated or constrained by the number of host species that a parasite can exploit. We test this hypothesis using a costructure approach, comparing two sympatric pinworm parasites that differ in host specificity - Parapharyngodon cubensis and Spauligodon anolis - on the Puerto Rican Bank and St. Croix in the Caribbean. Spauligodon anolis specializes on Anolis lizards, whereas P. cubensis parasitizes A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 99 publications
2
26
0
Order By: Relevance
“…In reality, the mechanisms of parasite diversification are still unclear, and other factors such as host density and host defence have also been linked with parasite diversification (Morand, ). Previous studies on Spauligodon nematodes have reported high population structure on islands, as a direct consequence of their specificity and diversification (Falk & Perkins, ). However, it remained unclear whether Spauligodon is in fact prevented by specificity barriers from expanding its host range, if it is somehow immune to the parasite island syndrome, or if sample bias had a strong influence on the observed patterns.…”
Section: Discussionmentioning
confidence: 97%
“…In reality, the mechanisms of parasite diversification are still unclear, and other factors such as host density and host defence have also been linked with parasite diversification (Morand, ). Previous studies on Spauligodon nematodes have reported high population structure on islands, as a direct consequence of their specificity and diversification (Falk & Perkins, ). However, it remained unclear whether Spauligodon is in fact prevented by specificity barriers from expanding its host range, if it is somehow immune to the parasite island syndrome, or if sample bias had a strong influence on the observed patterns.…”
Section: Discussionmentioning
confidence: 97%
“…, ; Miura et al . ; Falk & Perkins ). We demonstrated that N. georgenascimentoi corresponds to a species complex that includes at least three Neolebouria spp.…”
Section: Discussionmentioning
confidence: 99%
“…). Similarly, Falk & Perkins () (using 18S and COI) suggested that the differences in population structure between two Nematoda species ( Spauligodon anolis and Parapharyngodon cubensis ) are associated with a greater number of hosts, providing more opportunities for dispersal.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…However, if the hosts are particularly abundant, widespread and have high dispersal/mobility, the possibilities of gene flow for the parasites increase. In contrast, populations of parasites with a broad host range may show relatively high genetic variation and low differentiation because of a greater number of opportunities for gene flow (Archie andEzenwa 2011, Falk andPerkins 2013). Ecological or behavioural differences between host species may also influence the population genetic structure.…”
Section: Host Specificitymentioning
confidence: 99%